2019
DOI: 10.3390/su11143783
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability and Firm Performance: A Review and Analysis Using Algorithmic Pathways in the Throughput Model

Abstract: This paper reviews the prior research on the relationship between sustainability and a firm’s performance and proposes algorithmic pathways in the throughput model that could be used to improve the research findings for such research. Results of our literature search were mixed. Some studies reported a positive relationship between a firm’s sustainability efforts and profitability while others found a negative to no relationship. Studies found reasons for implementing sustainability even though it is a loss-be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 118 publications
0
3
0
Order By: Relevance
“…Building on two theoretical paradigms (responsible leadership theory and DRBV), this study makes several theoretical contributions to the literature on environmental sustainability related to perceived top management attributes and firm performance. First, by focusing on perceived top management attributes and introducing a new mediator in the relationship between top management beliefs and firm performance, we extend previous research that has focused on the direct relationship between sustainability management and firm performance (Rodgers et al, 2019; Sardana et al, 2020; Wiengarten et al, 2017). We argue that, although top management participation is conceptually related to top management beliefs, the level of sustainability adoption, and firm performance, it is better positioned to moderate the relationship between top management beliefs and the level of sustainability adoption.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Building on two theoretical paradigms (responsible leadership theory and DRBV), this study makes several theoretical contributions to the literature on environmental sustainability related to perceived top management attributes and firm performance. First, by focusing on perceived top management attributes and introducing a new mediator in the relationship between top management beliefs and firm performance, we extend previous research that has focused on the direct relationship between sustainability management and firm performance (Rodgers et al, 2019; Sardana et al, 2020; Wiengarten et al, 2017). We argue that, although top management participation is conceptually related to top management beliefs, the level of sustainability adoption, and firm performance, it is better positioned to moderate the relationship between top management beliefs and the level of sustainability adoption.…”
Section: Discussionmentioning
confidence: 59%
“…Although sustainability research has achieved advances by identifying the direct relationship between sustainability management and firm performance (Rodgers et al, 2019; Sardana et al, 2020; Wiengarten et al, 2017; Wong et al, 2020), little is known about the underlying mechanisms that translate environmental sustainability initiatives into better firm performance. To address the success of environmental sustainability development initiatives that organizations implement while pursuing firm performance, we looked at how employees perceive top management attributes like beliefs and support within the firm, how these employee perceptions impact organization‐level environmental sustainability performance, and whether such practices across organizations can better explain financial outcomes through higher environmental sustainability performance.…”
Section: Introductionmentioning
confidence: 99%
“…It provides a basic framework to support the idea that rewarding executive directors foster excellent performance at the company level (Conyon & Sadler, 2001). The previous literature (e.g., Kirsten & Toit, 2018;Rodgers et al, 2019) has shown contradicting findings regarding the relationship between executive compensation and performance, and additionally, studies on the banking industry in the USA and are rare (Nascimento et al, 2020). Therefore, this research contributes to the literature by filling these gaps.…”
Section: Impact Of Executive Compensation On Bank's Performancementioning
confidence: 97%
“…Numerous studies have identified a positive correlation between corporate sustainability and the financial performance of firms (Galimulina et al 2023), suggesting that companies that prioritise sustainability practices tend to outperform their competitors (Ioannou and Serafeim 2019; Ammer et al 2020). This can be attributed to several factors, including cost savings through energy efficiency and waste reduction, enhanced brand reputation and customer loyalty, increased employee engagement and productivity, and improved risk management (Rodgers et al 2019). However, there are also studies that have found a negative or no relationship between sustainability efforts and profitability.…”
Section: Corporate Sustainability and Firm Performance Relationshipmentioning
confidence: 99%